Magic of Vitamin C - Kaur, Rajinder; Singh, Paramvir; Kaur, Gurpreet (SCHOOL SCIENCE, 2014)
Vitamin C is an odourless, water-soluble antioxidant vitamin. Humans and some other primates cannot synthesise Vitamin C in their body as they lack enzyme (L-gulonolactone oxidase) which converts glucose into Vitamin C in the liver of certain animals (Burns, 1959). Most plants and animals can synthesise this vitamin. Human body procures this vitamin mainly from fresh fruits and vegetables and also from animal products. There are many health benefits of Vitamin C. It plays a vital role in normal functioning of the body. It helps in the formation of collagen, lowers blood cholesterol, regulates nervous system, formation of neurotransmitters and increases iron absorption in gut. Even a high dose of Vitamin C can help in preventing certain chronic diseases like heart disease, cancer, atherosclerosis, diabetes, cataracts and muscular degeneration. Vitamin C or Ascorbic Acid is a powerful antioxidant because it can form a stable free radical by donating hydrogen atom and protects body from harmful free radical pollutants (e.g., superoxide, nitric oxide and hydroxyl radicals) and other reactive species (e.g., hydrogen peroxide, peroxynitrite and hypochlorous acid